2022
DOI: 10.1186/s40168-022-01390-0
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of the short-chain fatty acid propionate on vascular calcification through intestinal microbiota remodelling

Abstract: Background Vascular calcification is a major cause of the high morbidity and mortality of cardiovascular diseases and is closely associated with the intestinal microbiota. Short-chain fatty acids (SCFAs) are derived from the intestinal microbiota and can also regulate intestinal microbiota homeostasis. However, it remains unclear whether exogenous supplementation with propionate, a SCFA, can ameliorate vascular calcification by regulating the intestinal microbiota. This study was conducted to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 102 publications
1
24
0
Order By: Relevance
“…57 Jianlong Yan et al found in their studies that Akkermansia was positively correlated with SCFAs in mice, and then the increasing SCFA may improve the intestinal barrier function and relieve inflammation. 58 Our conclusion was consistent with the above phenomena that after the intervention of 2′-FL, the significant reduction of Firmicutes , Lachnospiraceae , Ruminococcaceae , and Akkermansiaceae caused by FA was effectively relieved. These characteristic strains with variation may be the target of treatment for FA induced by OVA.…”
Section: Discussionsupporting
confidence: 91%
“…57 Jianlong Yan et al found in their studies that Akkermansia was positively correlated with SCFAs in mice, and then the increasing SCFA may improve the intestinal barrier function and relieve inflammation. 58 Our conclusion was consistent with the above phenomena that after the intervention of 2′-FL, the significant reduction of Firmicutes , Lachnospiraceae , Ruminococcaceae , and Akkermansiaceae caused by FA was effectively relieved. These characteristic strains with variation may be the target of treatment for FA induced by OVA.…”
Section: Discussionsupporting
confidence: 91%
“…41,65 On the other hand, normal contents of propionic acid have recently been linked to improved intestinal barrier function, decreased inflammation, and improved vascular calcification in rats. 66 The increase in propionic acid in our results may have been stimulated by the presence of fermentable sugars (FOS and GOS) present in the MNP.…”
Section: Discussionmentioning
confidence: 61%
“…In a vitamin D3 and nicotine-induced mouse model, supplementation with propionate of SCFAs lowers the levels of LPSs and protects the barrier to prevent the systemic inflammatory response triggered by intestinal “leakage”. 131 Furthermore, palmitoleic acid (rich in MUFAs) is not equivalent to palmitic acid, and there exists an antagonistic effect between them in terms of inflammation. The anti-inflammatory effects of palmitoleic acid are linked to LPS.…”
Section: Dietary Lipids and Intestinal Homeostasismentioning
confidence: 99%